Dinoflagellate cysts from surface sediments of Syracuse Bay (Western Ionian Sea, Mediterranean) - Rubino, Fernando; Belmonte, Manuela; Caroppo, Carmela; Giacobbe, Mariagrazia (Deep-sea research. Part II, Topical studies in oceanography, 2010)
The occurrence and abundance of dinoflagellate cysts were investigated for the first time at an Ionian locality along the south-eastern coast of Sicily, subject to spring–summer harmful algal events. Thirty-four cyst morphotypes were recognized belonging to 24 taxa identified at least at the genus level. Cyst abundance in surface sediments ranged from 43 to 828 cysts g −1 dry weight, with the highest numbers recorded at the most restricted station. Germination experiments allowed confirmation of species identification determined by cyst analysis and provided clonal cultures of Alexandrium minutum and Gymnodinium nolleri, two of the bloom-forming species in the area. This represents the first record of G. nolleri for the Mediterranean Sea.